(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article deals with the analysis of the notion of "binary opposition" and reveals its specificity. The author touches upon the universality of oppositional relations and analyzes the grounds of oppositions typology, analyzes functional-semantic, lexico-semantic, cognitive and other approaches to the study of oppositions.